A Theory of the Size and Shape of Nations - Friedman, David (Journal of Political Economy, 1977)
If territory goes to the nation which values it most as a source of revenue, nations will be shaped to maximize joint revenue, net of collection costs. Trade, as a major potential revenue source, should imply large nations; rent should imply small nations; and labor should imply that nations will have closed boundaries or be culturally homogeneous (to maximize exit costs). I show how this fits the pattern of European experience from Roman times to the present. Results of preliminary numerical tests of predictions of the theory are given.